2015
DOI: 10.1007/s11251-015-9346-9
|View full text |Cite
|
Sign up to set email alerts
|

Do we need teachers as designers of technology enhanced learning?

Abstract: In this special issue, five teams of researchers discuss different aspects of the teacher as designer of technology enhanced learning situations. This final contribution critically discusses if and how teachers as designers of technology enhanced learning might (not) be feasible or even desirable. The premise underlying this critical view is that technology enhanced learning should not be seen as 'special' in comparison to other forms of learning in the teacher's arsenal. Both practicing professionals and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 25 publications
4
57
0
9
Order By: Relevance
“…Expertise in the school would increase in terms of VLE user design and best practices could be shared across courses and modules through the design technologist who would work across courses. The framework is based on Kemmis and McTaggart's (1988) action research model, which involves participants' continuous collective self-reflective inquiry in a social situation to improve the rationality of educational practices.…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Expertise in the school would increase in terms of VLE user design and best practices could be shared across courses and modules through the design technologist who would work across courses. The framework is based on Kemmis and McTaggart's (1988) action research model, which involves participants' continuous collective self-reflective inquiry in a social situation to improve the rationality of educational practices.…”
Section: Model Developmentmentioning
confidence: 99%
“…Some fairly recent studies have been focussing on the role of teachers as designers of TEL (Kali and McKenney 2012;McKenney et al 2015;Svihla et al 2015). Kirschner (2015) argues that designing is considered integral to the teaching and learning process; however, our data revealed that academics may not always have the technical skills or aptitude of materialising them using multimedia designs within the VLE to enhance learning (Shank 2005).Some of the key barriers ascertained from the study particularly relate to the navigation and aesthetics of the user interface along with the clunky and clumsy user experience. Yet with the right know-how, VLE areas can be engineered to improve both of these key features.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been heightening discussion about design thinking and its potential for teaching and learning (Norton & Hathaway, 2015). Scholars and practitioners stress the need for applications of design in learning (Kirschner, 2015). But this discussion has remained vague, with little specifics or clarity about how design and education connect in teaching-I suggest one key way they connect, is in STEAM.…”
Section: Introductionmentioning
confidence: 99%